Strategi Komunikasi Dalam Penggalangan Dana Lembaga Swadaya Masyarakat "Kemitraan" - Adi Damae Prasetya (KOM & REALITAS SOSIAL, 2011)
This research aimed to identify (1) How the partnership implementing communications activities? (2) Assessing the marketing strategies used by the institutions in proposed program funds. (3) indentify stages of communication strategies and types of activities in fund raising (4) Evaluation of Communication Strategies used by the Kemitraan.Interviews, observation and data collection used as methods to analyse descriptively of the situation in Kemitraan. The results showed that the Kemitraan has potential experiences, staffs, administration, programs and access to gain trust from the donor. In the other side, the communication strategies used can be improved in the future to assure the availability of funds for this institution. Experiences and strategies used by Kemitraan can be as an example and comparison to other NGOs who are interested to study in fundraising and communication strategy.